ACID ATTACKS SURVIVORS IN PAKISTAN: A QUALITATIVE STUDY - Dr. Nazia Malik; Ms. Fozia Mumtaz; Dr. Saira Siddiqui; Dr. Basharat Ali; Dr Farhana Nosheen; Muhammad Tayyab (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The purpose of the study is to indicate the psychosocial and cultural experiences of women victims of Acid Attack in Pakistani society. They faced multiplies problems as they have facial disability owing to acid violence. By using of a qualitative research study design, five in-depth interviews were conducted with Acid attack victims’ women. They were selected with the help of a non-profit organization in Pakistan called, "Depilex Smileagain Foundation" (DSF). Five respondents (married and unmarried women) were selected by using purposive sampling technique. Their ages were from 25 to 55 years old. To collect the data, an interview guide was developed to conduct semi-structured in-depth interviews. For analysis purpose thematic analysis method was used to explore insight stories of acid attack women victims. The victims' perceptions revealed the male dominating psychosocial/cultural context of infirmity persist in Pakistani society. The victims described that in contemporary Pakistani society, masculine controlling, traditional patriarchy trends and disbelieving exist in their personal lives, particularly in relation to marriage, employability, equality, and seeking justice; however, respondents strongly support and appreciate the role of DSF in regaining their lost self-reliance following the attack, as well as some employability and skill development training and socioeconomic empowerment at DSF. Their life stories might be solicitous to the policy makers, government agencies and other stakeholders to know the interminable cultural pressures that women with facial disabilities face. Women Acid Attack victims’ psychosocial and economic rehabilitation is also the obligation of Govt. agencies, NGOs, and community activists.